169 Microfluidics cell squeezing enables human PBMCs as drivers of antigen-specific CD8 T responses across broad range of antigens for diverse clinical applications. (9th November 2020) - Maloney, Michael; Loughhead, Scott; Ramakrishnan, Amritha; Smith, Carolyne; Venkitaraman, Anita; Yee, Christian; Jacques, Miye; Yarar, Defne; Sharei, Armon; Bernstein, Howard; Hlavaty, Kelan; Myint, Melissa; et al.
Abstract : Background: Antigen-specific CD8+ T cell activity is critical for mounting an effective immune response in a wide range of indications, including immune-oncology and infectious diseases. Methods: To elicit antigen-specific CD8+ T cell activity, we used microfluidics cell squeezing (Cell Squeeze®) to deliver antigens directly to the cytosol of antigen presenting cells (APCs). Direct cytosolic delivery bypasses the need for cross-presentation and efficiently loads antigen into the major histocompatibility complex class I (MHC-I) pathway. The Cell Squeeze® platform is generally agnostic to cell type and material. Therefore, not only does microfluidic squeezing enable cell subsets within human peripheral blood mononuclear cells (PBMCs) to function as unconventional APCs, but it also enables us to efficiently investigate a wide range of antigens including whole protein, peptides, and mRNA. This 'plug and play' nature of the platform allows for broad application in multiple disease areas. Results: In human cells, we demonstrated that microfluidic squeezing of PBMCs enables effective delivery to the major cell subsets including T cells, B cells, NK cells and monocytes. Delivery of CMV and HPV16 synthetic long peptides (SLPs) resulted in robust in vitro responses of both CD8+ T cell clones and patient-derived memory populations. To broaden the impact of our PBMC-based cell therapy approach, we investigated several other antigens relevant to other disease areas. Additional materials we delivered via squeezing and demonstrated antigen presentation include neoantigens, M1 Influenza mRNA, and pp65 SLP. Cell Squeeze® platform is simple to use and amenable to scale up. We demonstrated that delivery and viability for research scale process ( 2 × 10 6 cells) is equivalent to delivery and viability of PBMCs processed at manufacturing scale ( 1 × 10 9 cells). Conclusions: Microfluidic cell squeezing of human PBMCs with antigenic material can be tailored to produce APCs that drive robust CD8+ T cell response against targets across multiple disease areas and has been scaled up for clinical use. SQZ-PBMC-HPV are currently under clinical evaluation for treatment of HPV16+ tumors.